Essays in financial econometrics and quantitative industrial organization - Rashid Nadimi, Soheil (Kansas State University, 2015)
This dissertation consists of one essay in financial econometrics and two essays in quantitative industrial organization. The first essay studies the relationship between stock return volatility and current and prior shocks to oil price volatility. We study the behavior of aggregate stock markets as well as individual industry sectors. Our results show that lagged stock return volatility is the main determinant of current stock return volatility in aggregate markets, with oil price volatility providing no additional information that can be used to forecast stock return volatility. For individual industry sectors, we find a robust and stable prediction relationship only for the chemicals industry. Additional estimation exercises confirm the robustness of these results. The second essay uses a Bertrand-Nash price-competition framework to models a vertically integrated provider (VIP) that is a monopoly supplier of an essential input for downstream production. An input price that is “too high” can lead to inefficient foreclosure and one that is “too low” creates incentives for nonprice discrimination. The range of non-exclusionary input prices is circumscribed by the input prices generated on the basis of upper-bound and lower-bound displacement ratios. The admissible range of the ratio of downstream to upstream “price-cost” margins for the VIP is increasing in the degree of product differentiation and reduces to a single ratio in the limit as the products become perfectly homogeneous. The third essay explores the relationship between upstream input prices and downstream market exclusion under a Stackelberg quantity-competition framework. Market exclusion is a concern when input prices are “too high” and “too low” because it can result in inefficient foreclosure and sabotage, respectively. Consistent with the results obtained in the second essay, the safe harbor range of downstream to upstream “price-cost” margin ratios is decreasing in the degree of product homogeneity and approaches a single ratio in the limit as the products become perfectly homogeneous. This single margin ratio preserves equality between the VIP’s wholesale and retail “price-cost” margins. A key finding for competition policy is that the bounds of non-exclusionary input prices are markedly wider under Bertrand-Nash competition than they are under Stackelberg competition. Hence, it is critical that the antitrust and regulatory authorities understand the nature of the industry competition so that rules governing permissible conduct are properly calibrated to yield efficient outcomes.
Keywords: Financial econometrics; Industrial organization; Economics (0501); Economics, Finance (0508)